Report and proceedings of the Symposium on aquaculture development - partnership between science and producer aáociations. Wierzba, Poland, 26-29 May 2004 held in connection with the European Inland fishery advisory commiáion twenty-third seáion Wierzba, Poland, 26 May - 2 Jun 2004 (EIFAC Occasional Paper (FAO), 2006)
Sumario (En)